Potential Effect of COVID-19 on Maternal and Infant Outcome: Lesson From SARS - Wang, Yun; Wang, Yiliang; Han, Xiaoxue; Ye, Jiazhuo; Li, Ruiman (Frontiers in Pediatrics, 2020)
The coronavirus disease 2019 (COVID-19) due to SARS-CoV-2 is highly infectious and its ongoing outbreak has been declared as a global pandemic by WHO. Pregnant women are susceptible to respiratory pathogens even in the development of severe pneumonia, suggesting the urgent requirement for assessing the potential maternal and infant outcome of the pregnancy with COVID-19. The intrauterine vertical transmission potential of SARS-CoV-2 also remains controversial. Herein, we discuss the potential effect of COVID-19 on maternal and infant outcomes based on current studies, including those published in Chinese, in a total of 80 mothers with COVID-19 and 80 infants. We also comprehensively explored the mother-to-child transmission routes of SARS-CoV-2, in particular the route of intrauterine vertical transmission. Given SARS-CoV-2 is a sister to SARS-CoV of the species SARS-related coronavirus, we made a comprehensive comparison between them to learn experiences from SARS. Although there is no evidence of supporting the intrauterine vertical transmission of SARS-CoV-2, our comprehensive analysis suggests that the adverse maternal and infant outcomes caused by COVID-19 cannot be underestimated. Further, we speculated that the inconsistency between nucleic acids and serological characteristics IgM to SARS-CoV-2 of infants’ specimens may be caused by the disruption of the amniotic barrier by the inflammatory factors induced by SARS-CoV-2 infection. Our review is beneficial to understand the effect of SARS-CoV-2 on maternal and infant outcomes.